Urgensi Akal Menurut Al Qur’an Dan Implikasinya Dalam Mencapai Tujuan Pendidikan Islam - M. Arif Setiawan; Malvien Zaenul Asyiqien (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2019)
Reason and the Qur'an know each other and are recognized in Islamic science. In this context, many researchers are interested in examining the relationship of reason and the Qur'an. According to Dr Muhammad Nahadi, discussion of reason, the Qur'an in the context of knowledge is the concept of developing knowledge. In line with this development, the development of Islamic education in the context of the study of reason and the Qur'an is urgently needed, especially as a means of answering the challenges of education with global challenges. This type of research is literature research, which is a form of scientific reasoning argumentation appearance that describes the results of literature studies and the results of the author's thought about a problem/topic of study. And data collection techniques using library research techniques, or library research, with data processing techniques. The data analysis process begins by gathering all data about the reason and objectives of Islamic education in order to find out the implications of reason in achieving the objectives of Islamic education. The results of this study indicate that, first, reason is the power of thought that when used can lead a person to understand and comprehend the problem he is thinking about. Second, reason serves as a tool for thinking, pondering and living also to develop ideas, concepts and bright ideas, very closely related to education. So that reason in its implications for the objectives of Islamic education is crucial to the